PERENCANAAN PENDIDIKAN DALAM MENUMBUHKAN KECINTAAN MEMBACA AL-QUR’AN DI GAMPONG CEUMPEDAK KECAMATAN COT GIREK - Saputra, Andika (Al-Madaris Jurnal Pendidikan dan Studi Keislaman, 2024)
Religious knowledge is a science that every Muslim, male and female, must be able to read the Koran, this is the beginning of education that must be given by parents to children, so the author is very interested in raising a title "The Role of PAI Teachers in Cultivating Love." "Reading the Koran to Students of SMP Negeri 2 Alue Gampong". Day by day, people's love of reading the Koran is decreasing. As a result, more and more people cannot read the Koran, let alone understand the contents of the Koran. In fact, studying the Qur'an can have a good influence on a person so that they become a Qur'anic teenager. Therefore, Islamic Religious Education Planning is very important in fostering a love of reading the Koran in society. The purpose of writing this journal is to find out the planning, obstacles faced, and efforts made by the Imam of Ceumpedak Village to foster a love of reading the Al-Qur'an in the Ceumpedak village community. The data source in this research is the Religious Chair of Ceumpedak Village. The data collection techniques in this research are through observation, interviews and documentation. Meanwhile, data analysis techniques use inductive methods, namely reducing data, presenting data, and verifying data or drawing conclusions.